2013
DOI: 10.1089/dia.2012.0257
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Insulin Resistance in Type 2 Diabetes Patients Regarding Oral Antidiabetes Treatment, Subcutaneous Insulin Injections, or Inhaled Insulin

Abstract: The acceptance of insulin is very low in type 2 diabetes patients. The option to inhale insulin increases the acceptability for some but not the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
0
25
0
8
Order By: Relevance
“…5 Petrak ve ark.nın yapmış olduğu ça-lışmada; diyabetli bireylerin %82'sinin önerilen insülin tedavisini reddettiği ifade edilmiştir. 6 Yine Polonsky ve ark.nın çalışmasında; insülin kullanan diyabetli bireylerin %28'inin reçete edilen insülin tedavisine başlamakta isteksiz oldukları bildirilmiştir. 7 Klinisyenler, hasta ve sağlık sistemi ile ilgili engeller nedeni ile Tip 2 diyabetli bireylerde insü-lin tedavisine uyum zorlaşmaktadır.…”
unclassified
See 1 more Smart Citation
“…5 Petrak ve ark.nın yapmış olduğu ça-lışmada; diyabetli bireylerin %82'sinin önerilen insülin tedavisini reddettiği ifade edilmiştir. 6 Yine Polonsky ve ark.nın çalışmasında; insülin kullanan diyabetli bireylerin %28'inin reçete edilen insülin tedavisine başlamakta isteksiz oldukları bildirilmiştir. 7 Klinisyenler, hasta ve sağlık sistemi ile ilgili engeller nedeni ile Tip 2 diyabetli bireylerde insü-lin tedavisine uyum zorlaşmaktadır.…”
unclassified
“…5 Diyabetli bireylerde PIR'nin gelişmesine neden olan faktörler olarak; kontrol kaybı duygusu, hastalığının kötüleştiğine inanması, kişisel başarısızlık duygusu, enjeksiyon anksiyetesi, insülinin etkili olmadığı algısı, kilo alma korkusu, hipoglisemi korkusu, insülin tedavisini yönete-meme, güven eksikliği, sosyal damga ve aile, iş ve arkadaşlar ile ilgili engeller gösterilmektedir. 5,6,9,11 Literatürde, Tip 2 diyabetli bireylerin insülin tedavisine başlamadan önce tedaviye karşı olumlu ve olumsuz algılarının değerlendirilmesi gerektiği vurgulanmaktadır. 9 Diyabetli bireylerin algılarının değerlendirilmesi ile hastaya öz yönetim ve davranış değişikliği sağlayabilecek etkili girişimler planlanabileceği belirtilmektedir.…”
unclassified
“…Another study used a standardized HR-QOL questionnaire to ask 532 T2D patients about potential additional drug therapy options [31]. Initially, patients compared the option of SC insulin with alternative OAA options.…”
Section: Used With Permission From Mannkind Corporationmentioning
confidence: 99%
“…As a second phase, researchers added inhaled insulin as a potential option, and this dropped patients' resistance to insulin therapy down to 57%. The paper concluded that while insulin therapy acceptance with T2D is low, that adding alternative delivery options may improve patient acceptance [31].…”
Section: Used With Permission From Mannkind Corporationmentioning
confidence: 99%
“…In addition, 70% of patients with T2DM consider it unlikely that they will require insulin treatment in the future [5]. Fear of hypoglycemia appears to represent the strongest barrier to insulin treatment [5][6][7][8][9][10]. Reduced flexibility, beliefs of insulin therapy permanence, and feelings of failure also represent obstacles for accepting insulin treatment [5,6,10].…”
mentioning
confidence: 99%